Pengaruh Apresiasi Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PT Sumbu Energi Abadi - Apriyani, Dewi Nisa (Pascasarjana Universitas Primagraha, 2023)
Human resources are the most valuable assets owned by an organization. Therefore, it is important to maintain it well, because the company's progress depends on the human resources it has. This research aims to analyze the influence of work appreciation and work motivation on employee performance. The method used in this research is associative research with a causality approach. The population in this study were employees who worked at PT Sumbu Energi Abadi Serang-Banten, namely 35 employees and the sample used was 35 respondents. Data analysis used SPSS version 26 software tools. The results of this research were that all hypotheses developed were well accepted, which means all hypotheses had a positive and significant influence.